Teaching elementary students real-life inquiry skills - Hill, Kristy (Libraries Unlimited, 2019)
This book shows how to teach elementary students to locate reliable information, evaluate sources, develop their writing skills in the classroom and in the library, evaluate information, and collect it from credible sources. It explains how to incorporate writing into your makerspace, encourage curiosity through the inquiry process, help students find their voice, and support writing and prewriting for digital media. Includes lesson plans, student samples, and activities.